(untitled) (International Journal of Biology and Chemistry, 2025)
There is an urgent need to preserve the ancient and culturally significant Kazakh dog breed Tobet, which is threatened with extinction. The evaluation of genomic instability and adaptive potential of Tobet dogs in comparison with outbred dogs as a model of genetic diversity and adaptability seems to be an interesting study and could shed light on the necessary efforts to improve the Tobet breed. In this context, the aim of this study was to analyze the cytological and cytogenetic (micronucleus test) parameters of peripheral blood cells of Tobet dogs and outbred dogs. The analysis revealed no significant differences in micronucleus frequency between Tobet and outbred dogs, indicating robust genomic stability. However, the observed cytological abnormalities, such as poikilocytosis, suggest potential health issues in the Tobet breed and highlight the need for continued health monitoring. This research underlines the importance of combining traditional breeding methods with modern genetic analyses to ensure the survival of the breed. Keywords: Tobet, purebred dog, outbred dog, genomic instability, adaptive potential, cytogenetic analysis.